Relationship between bone density of paranasal sinuses and adrenal steroids pattern in women during menopausal transition - Gargin, Vitaliy; Muryzina, Iryna; Shcherbina, Nikolay; Nechyporenko, Alina; Baryshevska, Victoria; Vorobyova, Olga; Alekseeva, Victoriia (Anthropological Review, 2020)
The course of menopause transition (MT) is associated with peculiarities of alterations occurring in a woman’s body, in particular, in the structure of bone tissue. Considering that bones of the paranasal sinuses (BPNSs) play a natural defense role against the spread of dental infection, their structure is important in dentistry. However, no information was found pertaining to changes of BPNSs during MT – a time when dental maladies increase in many women. The aim of our study was to collate density of BPNSs with status of adrenal steroids in women during MT, since the pattern of their changes determines the course of MT. Cross-sectional associations were examined between bone density of PNSs assessed by Spiral Computed Tomography and Serum content of testosterone (T), sex hormone binding globulin (SHBG), free androgen index (FAI), insulin, dehydroepiandrosterone sulfate (DHEAS), Adione, and Adiol in 113 women of perimenopausal age (age range from 45 to 55 years) who had already experienced premenopausal menstrual decline (amenorrhea less than 2 years). Strong positive (r = 0.73) correlation between minimal bone density of maxillary sinus in women with level of DHEAS was detected. It is important to note, that the correlation between minimal density of the lower wall of frontal sinus is a weak positive (0.3). Therefore , it can be suggested that bone tissue of the maxillary sinus is more sensitive to changes in DHEAS. The study showed that the level of male steroids, in particular DHEAS, affected the state of bone tissue in participants older than 50 years of age.